14 Diaphragmatic Electrical Activity in Preterm Infants on Non-Invasive High Frequency Oscillatory Ventilation (DEAP-NHFO Study). (29th October 2021) - Wong, Jonathan; Sasivimon, Soonsawad; Omar, Rawan Abu; Dunn, Michael; Ng, Eugene; Beck, Jennifer
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Continuous Positive Airway Pressure (CPAP) is a common form of non-invasive respiratory support for preterm infants. Non-invasive high frequency ventilation (NHFOV) is a relatively new method of non-invasive respiratory support. NHFOV is being increasingly utilized in clinical practice in an attempt to prevent intubation and minimize ventilator-induced lung injury in preterm infants. Preliminary studies suggest superiority of NHFOV over CPAP, but little is known about its mechanism of action and its effect on respiratory control in the newborn. We hypothesize that NHFOV reduces respiratory drive and improves ventilation, resulting in decreased patient diaphragm energy expenditure, which can be assessed by measuring the electrical activity of the diaphragm (Edi). Objectives: The objective of this study is to compare the effects of non-invasive respiratory support delivered by nasal CPAP versus NHFOV on respiratory pattern, as assessed by the Edi in very low birth weight (VLBW) preterm infants. Design/Methods: In a prospective, randomized, crossover study, 20 preterm infants with birth weights ≤1500 g requiring CPAP were randomized to either NHFOV or CPAP for 105 min, followed by crossover to the other method for the same duration. Edi was continuously measured by a feeding catheter with miniaturized sensors embedded in its wall (Maquet, Solna). The general sequence was 15 minutes for acclimation to the mode, 75 minutes for a feed to be completed, followed by 15 minutes for breath-by-breath analyses of neural breathing pattern. Primary outcome was difference in the peak Edi between CPAP and NHFOV. Secondary outcomes included difference in other measures of respiratory drive: neural respiratory rate, neural inspiratory time, diaphragm energy expenditure, transcutaneous pCO2, number of apnea episodes on the Edi, and episodes of clinically significant apnea. Results: No significant differences in Edi timing, Edi min, Edi peak, apnea, or CO2 were observed between the two modes of respiratory support. Conclusion: In this cohort of VLBW preterm infants, neural respiratory pattern was not significantly different between NHFOV and CPAP. With this baseline information in stable preterm infants, it would now be important to assess whether these results hold true in infants with more severe lung disease, where NHFOV is often used as escalating support from CPAP.